A new mode for an on-line determination of Amiloride in pure and pharmaceutical preparation using CFIA with homemade Ayah 3SBGRx3- 3D solar cell microphtometer analyzer. - TurkieAl-Awadie, Nagam S.; Alaloosh Alamri, Malik H. (Iraqi Journal of Science, 2023)
A new, simple, accurate, fast and sensitive spectrophotometric method has been developed for the analysis of amiloride in pure and pharmaceutical formulations by continuous flow injection analysis. The method was based on the oxidation of the drug with Ce(IV)sulfate in acidic medium to formed a pinkish-red color species which determined using homemade Ayah 3SBGR x3-3D solar cell flow injection photometer. Optimum conditions were obtained using a high intensity green light emitted diode as a source. The linear dynamic range for the instrument response versus amiloride concentration was 0.0005- 10 mmol.L-1 while the L.O.D was of 9.471 ng / sample. The correlation coefficient (r) was 0.9824 while percentage linearity (r2%) was 96.50%. RSD% for the repeatability (n=8) was lower than 1.5% for the determination of amiloride, at concentration of 0.5 mmol.L-1. The method was applied successfully for the determination of amiloride in pharmaceutical preparation. A comparison was made between the newly developed method and the classical method (UV-Vis spectrophotometry at wave length 540nm) of analysis using the standard additions method via the use of paired t-test. It showed that there was no significant difference between the quoted value of each individual company with calculated t-value at 95% confidence interval from developed method, in addition to comparison between two methods and calculate t-value, it was noticed that there no significant difference between two methods at 99% but a significant difference at 95% confidence level.